'F&#% autonomy': Houellebecq, Submission, and Enlightenment's 'last dismaying dregs'. (2nd January 2019) - Betty, Louis
ABSTRACT: This article examines the evolution of Houellebecq's treatment of History across the span of his novels. Focusing in particular on The Elementary Particles, The Map and the Territory, and Submission, I explore a gradual but discernible movement away from a broadly Comtean understanding of historical destiny, which anticipated the decline of theology and metaphysics and the rise of positivism. Over the course of Houellebecq's novels, this account of historical evolution yields to a circular rendering of history in which theology and metaphysics alternate as religious and secular dispensations trade power. While The Elementary Particles imagines the techno-utopian fantasy of a genetically perfected humanity, Submission abandons these Comtean-inspired utopian ambitions for a religiously grounded social order maintained under Islam. Crucially, I contend that François' journey towards conversion in Submission, foreshadowed by the character Houellebecq's conversion to Catholicism in The Map and the Territory, may be read as a narrative of the West's exhaustion with Enlightenment and the burdens of personal autonomy. Submission is a novel that doubts the positivist pretention that humanity can move beyond religion and metaphysics, and instead suggests that metaphysics and its attendant doctrine of individual rights and freedom inevitably collapses back into theology.